2014
DOI: 10.1002/eco.1500
|View full text |Cite
|
Sign up to set email alerts
|

Demodulation of time series highlights impacts of hydrologic drivers on the Everglades ecosystem

Abstract: In the context of climatic uncertainty and potential climatic change, incorporating climatic variability and change in eco‐hydrological analysis, as well as understanding the impact of such variability on ecosystems, is of crucial importance. The latter is particularly true for those complex ecosystems, such as wetlands, which cradle large varieties of species, many of which rare or endangered. Focusing on the Everglades wetlands, we investigate the presence of non‐stationary elements in the seasonal cycle of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…The influence of rainfall as the primary driver of water levels presented in this study are consistent with previous research conducted in the southern Everglades. For example, time-series demodulation using Fourier analysis was conducted at a variety of well sites in the northern and southern Everglades and revealed that stage levels are directly impacted by rainfall, with large fluctuations in rainfall directly translating to large fluctuations in stage levels (Foti et al, 2015). Likewise, a water balance constructed by Zapata-Rios & Price (2012) indicated that precipitation was the greatest source of water into Taylor Slough.…”
Section: Changes In Groundwater Levels As a Function Of Restorationmentioning
confidence: 99%
“…The influence of rainfall as the primary driver of water levels presented in this study are consistent with previous research conducted in the southern Everglades. For example, time-series demodulation using Fourier analysis was conducted at a variety of well sites in the northern and southern Everglades and revealed that stage levels are directly impacted by rainfall, with large fluctuations in rainfall directly translating to large fluctuations in stage levels (Foti et al, 2015). Likewise, a water balance constructed by Zapata-Rios & Price (2012) indicated that precipitation was the greatest source of water into Taylor Slough.…”
Section: Changes In Groundwater Levels As a Function Of Restorationmentioning
confidence: 99%